The Hospital Problem : the Report of a Special Conference of Labour, Hospital, Medical and kindred Societies (London : The Labour Party ; printed at the Office of the British Medical Association, 1924)
1924 1924 1920s 12 pages 11 fifty years their work had been so greatly extended that they provided over 75 per cent. of the hospital accommodation in the country. Latterly the rate-aided hospital had started to deal with general illness in the community, and a similar and parallel service to that of the voluntary hospitals had been set up. The necessity for careful co-ordination and correlation between all the agencies for the relief of sickness and the amelioration of the physical condition of the people was therefore apparent. The need for general hospital accommodation varied greatly in different parts of the country. In the rural counties it was not so great as in the more thickly populated centres. In all centres, however, there was admittedly a deficiency in hospital accommodation, and the deficiency was greatest in the newer industrial areas of England. The voluntary foundations in the older cities and towns were generally better able to cope with the need than the more recently established voluntary institutions in the new industrial areas. This point was well illustrated in the case of Bradford, where the only general hospital in the city contained less than 200 beds and served a population of about 300,000 in the city and anything from 100,000 to 200,000 in the district outside. For many years the working-class population were forced to resort to the Poor Law infirmary because of the scarcity of general hospital accommodation. They did so unwillingly, and in numerous cases refused to go there at all. The hospital problem became probably more acute in this district than in most other localities in England, and the Bradford City Council desired to find relief for it. Let it be remembered that the voluntary hospital, good as it was, had fewer than 0.5 beds per 1,000 of the population. The alternative was the Poor Law infirmary, and although the guardians did everything they could to make it efficient they could not get rid of the Poor Law name and atmosphere. The city council and the infirmary authorities conferred as long ago as 1913, but on account of the war no steps were taken. At the termination of the war the city council and the Poor Law authority came together by mutual agreement, and the Poor Law authority handed over its well equipped hospital, which had been used as a war hospital during the war, to the city council for use as a general hospital. Dr. Buchan wished to disabuse the British Medical Association of the idea that "This is socialistic Bradford; these are the terrible Bolsheviks of the North." No; this was not the work of Bolsheviks; it was done by the unanimous wish and consent of hard-headed Yorkshiremen who knew how to drive a bargain. Of the three men who were most intimately concerned in the negotiation one was a Conservative, one a Liberal, and the other a member of the Labour party. The city council, having got the hospital, determined not merely to change its name but to staff and equip it like the best hospitals in the country (which were the voluntary hospitals). The city council received from the Poor Law authority the sick poor, but no differentiation was made in the hospital between the Poor Law and what he called the civic cases. The growth of the work of the hospital might be seen from the following table : Admissions in Poor Law. Civic. Total. 1920 ... 2,290 1,514 3,804 1921 ... 1,869 2,613 4,482 1922 ... 1,559 3,582 5,141 1923 ... 1,505 4,103 5,608 No difficulty had been found in administering the hospital from a medical point of view, although the supply of patients came from these two sources: on the one hand, from the general population, on the recommendation of the patients' own medical attendants; and on the other, from the Poor Law guardians on the order of the relieving officer. The cases admitted through the Poor Law had been almost invariably cases requiring some additional form of relief, either for the patients or their families. The hospital was meeting moderately the needs of the population. In Bradford, as elsewhere, they wanted the voluntary movement to go on. They had not tried to compete with the voluntary hospital so as to close it down. The staff at the municipal hospital was very much the same as the staff at the voluntary hospital. There was quite a good feeling between the two staffs. At the time the municipal hospital was started an artificial agitation was set up to stop the municipality from going on with the work. He knew from the beginning that this agitation was artificial and that it would fail. The hospital had not been in existence three months before it was evident that the venture would justify itself. An effort had been made to bring general practitioners into the organization, and indeed general practitioners did come up for consultation at the hospital; but the general practitioner, of course, had to face the claims of his own practice and to make a livelihood, and there was difficulty in making arrangements — much as the hospital authorities wished to make them — whereby practitioners could actively co-operate. In conclusion, he said that the hospital was worked as an integral part of the health work of the corporation, and had been of material benefit in correlating the medical and health services. The hospital had won for itself a high local reputation, and the ease with which admission was gained to it had contributed largely to its success. Dr. E. A. Gregg was glad that the opener had referred in quite appreciative terms to the work of the guardians. He thought that the guardians had been unnecessarily criticized at that conference; they did not deserve the harsh things which were said about them by Lord Knutsford and others. In one Poor Law institution with which he was acquainted the spirit was most happy, and the harshness of the Poor Law regime was not nearly so much in evidence as people thought. The stigma, of course, remained; one way to remove the stigma would be to bring in the general practitioner and enable him still to see those patients whom he had seen before admission. Mr. Bishop Harman said that with regard to the Bradford controversy the contention or objection of the doctors to Dr. Buchan's scheme arose from the way in which it was initiated. Dr. Buchan or his authority tried to ride roughshod over everybody in the district. From this there arose the hospital policy of the British Medical Association. Far from being antagonistic to the work of the State in these matters, the British Medical Association was anxious that the State work should be directed into the most profitable channels. He believed that the task before the nation in various fields, not in hospitals alone, was so enormous that no voluntary organization could possibly tackle it alone. Nor could the State deal with it alone without voluntary help. The Association was not against State action in its proper sphere. Sir Thomas Neill referred to the "scandal" of East London, where the London Hospital had a long waiting list while a Poor Law infirmary opposite had two hundred empty beds. Dr. F. E. Fremantle, M.P., spoke of the Parliamentary fence which had to be got over before any scheme for State-aided hospitals came into being. The movers along this line had not yet taken into account the difficulties that might be raised in Parliament. The report of the Labour party definitely proposed to combine voluntary and State hospitals, but the difficulty really came in with regard to financial provision. What was proposed in the Labour policy would run to hundreds of millions of pounds. The first thing Parliament would want would be an estimate, and there were no estimates in the Labour party pamphlet. Immediately estimates were forthcoming there would be objections from other interests because, should the estimates go through, reductions of taxes in certain directions would not be possible, or grants for other objects would have to be withheld. He believed that it would be best to link up this proposal with an extension of national health insurance. Mr. H. Lesser (Hospital Saving Association) described the work of the body he represented, particularly in South London, where in one works there were 6,000 persons interested in the scheme. People at first were slow to appreciate its value, but once the appreciation was gained, the support was steady and increasing. He fell foul of one sentence in the Labour pamphlet, which was to the effect that employers took note of those of their workmen who were not subscribing to a contributory fund and penalized them. This was a libel on employers. Dr. C. Buttar said that it was most refreshing to hear, as they had heard from Mr. Lesser, any advocacy of the voluntary system. Often those who should be its advocates appeared to think that the system was bound to fail on financial grounds. There was no real reason why the voluntary system should fail, and it ought to be quite possible to set it on its legs without recourse to anything except purely voluntary measures. So many of the addresses at that conference had been tinged with the desire for State interference or State control or State aid as a necessary preliminary to securing a more healthy community or a more efficient service; but when one came to investigate these assumptions nearly all of them were found to be quite wrong. He detected a desire for State aid in the argument of Lord Knutsford and of Mr. Bishop Harman, as well as in that of a "case-hardened bureaucrat" like Dr. Buchan. He wished the hospitals to remain without State aid at all, and he favoured contributory schemes on the one hand, and on the other the persuading of people of means to endow beds and research. If this were done the hospitals would remain on a voluntary basis and no more would be heard about State aid. Dr. Buchan, in reply, said that his contentions did not appear to have been seriously controverted. The British Medical Association had formulated its policy after the matter was an accomplished fact. He thought there could be no greater mistake than to throw the hospitals into the hands of the doctors alone. The hospital which enjoyed the entire confidence of the public was one which had a considerable body of laymen to manage it, not one that was run by medical men alone. (" Hear, hear.") 36/L41/1/8